(3OjhGf MSjf Hf QTjO GdQVhjs - (3GdQVhj , MSjf Hf QTjO Hf bGSe GdMSjfj Gdfbhjs ((3CMeO Hf MHjH GdSGLfj s)
(3ChdgG (B:s
(3fMeOc Gddge efTF GdCee hHGSW GddhM hHGQF Gdbde hgPg bUGFO YOjOI HOjYI aj afgG aQjOI s
(3BNQgG (B:s
(3heHfi GdTLQI Ydi gPG GdHjJ(B: (3jG LeGd GdCYjGO gfjJ YjOkG Hc bO RjO HgLI hLeGdkG s
(3HChd GdfSNI agQSJs
(3cGf GdeDda MjkG SfI (B1156(3g``s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B7s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B83 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs